Correlation between Computerized Tomography Densimetry and Histomorphometry in Assessment of Bone Healing - Aljumaily, Mahmood A; Alnuaimy, Hatim; Al-allaf, Hazim (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Assessment of fracture healing is a common problem in orthopedic practice and research. Computerized Tomography (CT) is a reliable tool for quantification of the fracture repair process in experimental animals. Histomorphometric evaluation provides a clear quantitative evidence of the bone healing process. The evaluation by micro-architectures in healing bone showed variable correlation between CT and histomorphometry.Material and methods: open ulnar osteotomy induced in twenty young male rabbits under general anesthesia without internal fixation, and divided into five groups. A group of animals were sacrificed at end of 2nd week, 3rd week, 4th week, 5th week, and 6th week. The right ulna isolated and the bone specimens taken for radiological examination, CT scan densimetry and histomorphometric evaluation carried out for the callus at the site of osteotomy for all animals in both group.Results: The mean of histomorphometric evaluation of callus at the site of ulnar osteotomy at the end of second week were 2.9, and increased with duration to reach 9.3 at end of sixth week. The mean of CT densimetry of callus in site ulnar osteotomy at the end of second week were 96.2, and increased with duration to reach 723.3 at end of sixth week. The correlation coefficient between histomorphometric evaluations of callus in site ulnar osteotomy and value of CT densimetry measurements was 0.958, which considered very highly significant, (the P value < 0.0001).Conclusion: The present study demonstrate that, there is strong correlation between CT scan bone densimetry of callus in site of osteotomy and the results of histomorphometric evaluation of callus. The CT scan bone densimetry of callus can be used to assess the bone healing in experimental and clinical studies, as it is noninvasive technique.